Ecclesiastical Law, Clergy and Laity - Patterson, Neil, author.
1 online resource (194 pages)
Keywords: Discipline in an ecclesiastical context can be defined as the power of a church to maintain order among its members on issues of morals or doctrine. This book presents a scholarly engagement with the way in which legal discipline has evolved within the Church of England since 1688. It explores how the Church of England, unusually among Christian churches, has come to be without means of effective legal discipline in matters of controversy, whether liturgical, doctrinal, or moral. The author excludes matters of blatant scandal to focus on issues where discipline has been attempted in controversial matters, focussing on particular cases. The book makes connections between law, the state of the Church, and the underlying theology of justice and freedom. At a time when doctrinal controversy is widespread across all Christian traditions, it is argued that the Church of England has an inheritance here in need of cherishing and sharing with the universal Church.The book will be a valuable resource for academics and researchers in the areas of law and religion, and ecclesiastical history. .